Analisis Dan Perancangan UI/UX Berbasis Teknologi Pada Company Profile Medicom Untuk Meningkatkan Aksesibilitas Dan Pengalaman Pengguna - Akmal Firmansyah; Ilham Budi Trisetyo; Rizqya Chandra Muji Pratama; Fajar Mahardika (INFOKABIN (Informatika, Komputasi, Aplikasi dan Bisnis), 2026)
The development of digital technology requires that PNC Student Activity Units (SAU) have a digital company profile that is not only informative but also easily accessible and provides an optimal user experience. This study aims to analyze and design technology-based UI/UX for the SAU company profile, focusing on improving accessibility and user satisfaction. The method used is User-Centered Design (UCD), including data collection through questionnaires and interviews with members, analysis of user needs, and development of an interactive prototype using responsive modern web technologies. Usability testing on 30 respondents showed an increase of 32% in user satisfaction scores and 29% faster information access compared to the previous version. The ease of navigation received an average score of 4.5 out of 5, indicating a significantly improved user experience. These findings demonstrate that implementing technology-based UI/UX design can enhance accessibility, efficiency, and user engagement in accessing SAU information within PNC